Experimental investigation of the effect of airgaps in preventing desiccation of bentonite in geosynthetic clay liners exposed to high temperatures. Issue 2 (April 2019) - Yu, Bowei; El-Zein, Abbas
Abstract: This paper investigates whether the introduction of an airgap above a composite liner made of a geomembrane (GMB) and a Geosynthetic Clay Liner (GCL) can decrease thermal loads on the GCL, reduce the risk of bentonite desiccation and/or help maintain its low hydraulic conductivity. A composite liner, subject to 20 kPa overburden load, over a well graded sand was subjected to a thermal gradient. In addition, to the reference base case in which no airgap was present, two designs included air gaps through the placement of a 10 mm and 20 mm-thick geocomposites (GC) on top of the GCL-GMB, respectively. Temperatures on top of the GCLs were found to be significantly reduced by the presence of air gaps, relative to the reference base case. All three designs resulted in GCL desiccation cracks at the end of the tests, due to the relatively high temperature gradients and low water retention of the subsoil, even in the presence of air gaps. However, X-Ray imaging revealed that crack patterns in bentonite samples from designs with air gaps were finer and narrower. Subsequent rehydration (and permeation tests) with distilled water indicated that significant self-healing of bentonite was in evidence in all three cases. However, while in the absence of an air gap the saturated hydraulic conductivity was found to be 2.8 times its pre-heating value, no significant increase was recorded for other two cases. X-Ray imaging of rehydrated samples confirmed that more effective healing had occurred in samples with an air gap.